Recycling of Polyethylene Bags into High‐Strength Yarns Without Using Melt Processing. Issue 2 (5th November 2019) - Xu, Qiaoli; Yi, Hongling; Gao, Xingzhong; Shi, Jing; Yao, Donggang
Abstract : A critical issue facing mankind is how to effectively recycle plastic grocery bags. Currently, the most proven practice for bag recycling is to create numerous returning sites throughout the nation. However, the success is compromised by the voluntary nature of such activities. In this work, we investigate an alternative approach to bag returning, by diverting recycling activities directly to consumers or end users at home. Specifically, a simple process for converting waste bags into high‐strength fibers and yarns is designed and tested in an experimental feasibility study. The results from tensile testing and thermal analysis demonstrate that by a combined process sequence of cutting, knotting, twisting, hot drawing, and heat setting, high‐strength polyethylene yarns with mechanical properties comparable to those of melt‐spun polyethylene fibers can be produced. Without the involvement of melt processing, yarns made of a waste high‐density polyethylene grocery bag material were hot drawn and heat set to achieve a tensile strength of 330 MPa. Yarns with such ternacity are expected to find numerous applications in textile, flooring, and leisure products. This may open up a new paradigm in plastic bags recycling and allow part of the recycling burden to be shifted to local residential communities. POLYM. ENG. SCI., 60: 281–287, 2019. © 2019 Society of Plastics Engineers